Bureaucratic Challenges in the Implementation Network of Food Diversification Policy in Indonesia - ., Alwi; Susanti, Gita; Sopia, Novayanti (KnE Social Sciences, 2023)
Network governance is an approach that can be used to overcome wicked problems and eliminate the main challenges of the bureaucracy, in the form of limited resources and strict regulations, in the delivery of public services and policies that involve multistakeholders. This study aims to explain the effectiveness of stakeholder interactions in the Food Security Council as a network governance mechanism. This study uses a qualitative design and a case study strategy to explain the challenges of bureaucracy in this policy. The data processing technique used is data reduction through data categorization and classification. Then, the pattern matching analysis technique is the theoretical pattern of the effectiveness of network governance. The results showed that the implementation of the food diversification policy was not yet effective. It can be showed that they do not try to build a collaborative food diversification program as a solution program for food problems. This is due to the lack of understanding of this mechanism, the lack of trust among them, many members and varying interests, unclear consensus network goals, and this mechanism is still weak in coordinating and facilitating interdependent action. Keywords: Food diversification; policy; regulations; public services